2023
DOI: 10.1002/lim2.79
|View full text |Cite
|
Sign up to set email alerts
|

How do caregivers of children living with HIV/AIDS cope, and where do they get support?: A qualitative study in Ghana

Abstract: BackgroundCaring for children living with human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS) is challenging and has a tremendous impact on the physical and psychological health of caregivers. Caregivers of children with HIV/AIDS need to adopt coping mechanisms to navigate these complexities as it influences the quality of care provided. The literature on coping strategies and support (formal and informal) available to caregivers of children living with HIV/AIDS is scant. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
3
0
2
Order By: Relevance
“…People who are very spiritual may find it easier to use a variety of religious coping mechanisms under pressure (such as prayer, meditation and religious assessments). 30 , 31 , 32 , 36 , 37 , 38 Scientific evidence in this study revealed that caregivers benefitted from using prayer and singing of gospel songs as a weapon to battle all difficulties that interfered with their abilities to discharge effective and efficient caregiving HIV/AIDS orphans. However, it is not always the case that religious practices are the only hope that can be relied upon to overcome the challenges.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…People who are very spiritual may find it easier to use a variety of religious coping mechanisms under pressure (such as prayer, meditation and religious assessments). 30 , 31 , 32 , 36 , 37 , 38 Scientific evidence in this study revealed that caregivers benefitted from using prayer and singing of gospel songs as a weapon to battle all difficulties that interfered with their abilities to discharge effective and efficient caregiving HIV/AIDS orphans. However, it is not always the case that religious practices are the only hope that can be relied upon to overcome the challenges.…”
Section: Discussionmentioning
confidence: 85%
“… 30 , 31 To support this notion, a phenomenological study conducted in Ghana established that neighbours were always available whenever the caregivers of HIV/AIDS orphans failed to cope with caring demands and needed someone with whom to communicate. 32 The neighbours showed ubuntu by offering the caregivers of HIV/AIDS orphans emotional support when they were trapped in a difficult situation. 33 Thus far, evidence from the current study clearly verified that neighbours did not turn their back against caregivers of HIV/AIDS orphans during difficult times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil ini sejalan dengan penelitian Atanuriba et al (2023) di Ghana bahwa strategi koping yang dilakukan keluarga adalah koping spiritual dengan berdoa minta pengampunan kepada tuhan untuk keluarga dengan ODHA, berupaya untuk bangkit dan mengatasi masalah yang ada. 32 Hasil penelitian ini berbeda dengan hasil penelitian Soliha & Masfi (2020) menyatakan bahwa beberapa keluarga memilih untuk menghindari koping dan mengisolasi anggota keluarganya karena malu sehingga penerimaan ODHA di keluarga menuju ke arah yang negatif. 33 Hasil penelitian, sebagian besar keluarga tidak mendapatkan dukungan dari siapapun dalam merawat ODHA karena identitas penyakit yang dirahasiakan dan dijauhi keluarga jika mengetahui ada anggota keluarga dengan ODHA.…”
Section: Tema 4 Koping Dan Dukunganunclassified
“…Keluarga tidak memberikan dukungan fisik atau finansial yang sangat diharapkan oleh para caregiver, sementara pemimpin komunitas dan LSM tidak selalu hadir untuk memberikan dukungan. 32…”
Section: Tema 4 Koping Dan Dukunganunclassified